Performance reduction and discrepancies between supported and suspended 1D photonic-crystal/photonic-wire with medium extended microcavity length - Nawi, Mohd N.; Berhanuddin, Dilla Duryha; Mahdi, Mohd Adzir; Yeop Majlis, Burhanuddin; De La Rue, Richard M.; Md Zain, Ahmad Rifqi (S P I E - International Society for Optical Engineering, 2021)
We report the performance of silicon-on-insulator medium-length extended microcavity (3 to 4.5  μm long) one-dimensional photonic crystal waveguide. Quality-factor (Q-factor) values ranging from 2000 to 37,000 were observed. The waveguides/wire were fabricated using an inductively coupled plasma reactive ion etching with SF6 and C4F8 gasses. Optical transmission of the design is heavily influenced by the surface roughness of the waveguide wall. We achieved a good free spectral range control for resonance frequency separations in between 39 and 65 nm. Supported and suspended microcavity structures for the case of a medium-length extended microcavity were compared. We observed an inferior performance in terms of the optical transmission and Q-factor in the latter. We have selected 4-μm microcavity length for comparison. The suspended structure was obtained by utilizing the wet etching technique on the same device. A high Q-factor value of ∼26,000 was observed in one of the resonances excited for cladding-layer supported extended microcavity. However, the Q-factor was reduced to ∼17,000 after removing the silica cladding beneath the silicon waveguide core.